Da compensação ambiental na lei nº 9985/2000 que trata do sistema nacional de unidades de conservação. - Macedo, Laíse Helena Silva (2017)
This paper intends to discuss the most frequent problems related to environmental compensation established in article 36 of Law 9.985 / 2000, which created the National System of Conservation Units (SNUC). The issue of great relevance in the national juridical environment system seeks to identify the main problems in the use of environmental compensation to finance the System of Conservation Units. In practice, means are sought to obtain resources from entrepreneurs who want to develop activities that impact the environment to maintain and create new areas to be preserved in Brazil. The Institute came up with Conama Resolution 10/87, which required only those projects that reached forests or other ecosystems, expanded by Resolution Conama 2/96, which allowed the use of resources in other public conservation units, not only in the Station Ecological. The main problems of the environmental compensation institute will be here observed in practice and many doubts shall be presented regarding the institute and its applicability. In this sense, it is investigated if the institute follows the strict legal orientation and what the grounds, objectives and legal nature of the environmental compensation under the terms of art. 36 of the SNUC. The work will benefit from the doctrine and jurisprudence and the positions of the STF and the TCU in the delimitation of questions related to the institute. The method used here will be hypothetic and deductive and the methodology will be predominantly bibliographical.